Reconciling resilience across ecological systems, species and subdisciplines. (15th September 2021) - Capdevila, Pol; Stott, Iain; Oliveras Menor, Imma; Stouffer, Daniel B.; Raimundo, Rafael L. G.; White, Hannah; Barbour, Matthew; Salguero‐Gómez, Roberto
Abstract: Resilience has emerged as a key concept in ecology and conservation biology to understand and predict ecosystem responses to global change. In its broadest sense, resilience describes the ability of an ecosystem to resist, and recover from, a disturbance. However, the application of such a concept in different subdisciplines of ecology and in different study systems has resulted in a wide disparity of definitions and ways of quantifying resilience. This Special Feature, which spans the Journal of Ecology, Journal of Animal Ecology and Functional Ecology, provides an overview of how ecologists define, quantify, compare and predict resilience across different study systems. The 29 contributions to this Special Feature show the broad range of approaches used by ecologists to study resilience. Almost half of the contributions (48%) study resilience at the community level, with a 30% of them studying resilience at multiple levels of biological organisation. A large proportion of these articles are observational (42%), experimental (14%) or a combination of both (17%) while a 17% utilise theoretical or computational approaches. Although 38%, 21% and 14% of the studies were based solely on plants, animals or micro‐organisms, respectively, 17% of them incorporated these multiple trophic levels. Synthesis . A unified ecological understanding of resilience across systems and taxa requires a trans‐disciplinary consensus on what resilience actually is and how to best measure it. Here, we provide an overview of how ecologists define, quantify, compare and predict resilience across different ecological systems and subdisciplines, with reference to the diverse approaches used by contributions to this Special Feature. We identify four key recommendations to harmonise future efforts in resilience research: (a) define resilience using existing theoretical frameworks; (b) use common and comparable metrics to measure resilience; (c) clearly contextualise and define the pre‐ and post‐disturbance state of the ecological system and (d) consider explicitly the disturbance type and regime impacting the system. Abstract : In this Editorial, we discuss current perspectives on resilience, and both theoretical and empirical approaches to studying it, across the 29 manuscripts published in this joint Special Feature. From these contributions, we identify the main challenges and opportunities in resilience research, as well as ways to bring consensus to the field. Resumen: La resiliencia ha surgido como un concepto clave en ecología y biología de la conservación para comprender y predecir la respuesta de los ecosistemas al cambio global. En su sentido más amplio, la resiliencia describe la capacidad de un ecosistema para resistir y recuperarse de una perturbación. Sin embargo, la aplicación de este concepto en diferentes subdisciplinas de la ecología y en diferentes sistemas de estudio ha resultado en una gran variedad de definiciones y formas de cuantificar la resiliencia. Esta edición especial, que comprende las revistas Journal of Ecology, Journal of Animal Ecology y Functional Ecology, proporciona una descripción general de cómo los ecólogos definen, cuantifican, comparan y predicen la resiliencia en diferentes sistemas de estudio. Las 29 contribuciones a esta edición especial muestran la amplia gama de enfoques utilizados por los ecólogos para estudiar la resiliencia. Casi la mitad de las contribuciones (48%) estudian la resiliencia a nivel de comunidades ecológicas, y un 30% de ellos estudia la resiliencia en múltiples niveles de organización biológica. Una gran proporción de estos artículos son observacionales (42%), experimentales (14%) o una combinación de ambos (17%), mientras que un 17% utiliza enfoques teóricos o computacionales. El 38%, 21% y 14% de los estudios se basaron únicamente en plantas, animales o microorganismos, respectivamente, el 17% de ellos incorporaron estos múltiples niveles tróficos. Síntesis . Una comprensión ecológica coherente de la resiliencia de distintos sistemas y taxones requiere un consenso transdisciplinario sobre qué es realmente la resiliencia y cómo se puede cuantificar. En esta editorial proporcionamos una descripción general de cómo los ecólogos definen, cuantifican, comparan y predicen la resiliencia en diferentes sistemas ecológicos y subdisciplinas, con referencia a los diversos enfoques utilizados por las contribuciones a esta edición especial. Identificamos cuatro recomendaciones clave para armonizar los esfuerzos futuros en la investigación de la resiliencia: (a) definir la resiliencia utilizando los marcos teóricos existentes; (b) utilizar métricas comunes y comparables para medir la resiliencia; (c) contextualizar y definir claramente el estado anterior y posterior a la perturbación del sistema ecológico; (d) considerar explícitamente el tipo de perturbación y el régimen de impacto al sistema.